2015
DOI: 10.1016/j.elerap.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The influence of parents versus peers on Generation Y Internet ethical attitudes

Abstract: Note: All research procedures were conducted in accordance with the ethical guidelines of the host country. 2 AbstractWe examine the role of parental style vs peer influence on Generation Y's attitudes towards online unethical activities using a survey of a matched parent-child sample.Results suggest that a protective parental style has the greatest impact on Generation Y's online ethical attitudes, while a strict discipline style has no significant influence.Peers are more influential, but not as influential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 85 publications
2
12
0
Order By: Relevance
“…These results suggest that especially peers and to a certain extent also favorite celebrities are important role models for adolescents’ online behavior directed at celebrities. These results are consistent with findings of previous studies showing that adolescents attach more importance to the opinions and reactions of their friends and peers than to those of their parents and teachers (Heirman & Walrave, 2012; Mitchell et al, 2015; Pabian & Vandebosch, 2014). Further research is necessary to investigate the prevalence of peers’, parents’, and celebrities’ negative online behavior directed at celebrities and how often adolescents are exposed to this behavior.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results suggest that especially peers and to a certain extent also favorite celebrities are important role models for adolescents’ online behavior directed at celebrities. These results are consistent with findings of previous studies showing that adolescents attach more importance to the opinions and reactions of their friends and peers than to those of their parents and teachers (Heirman & Walrave, 2012; Mitchell et al, 2015; Pabian & Vandebosch, 2014). Further research is necessary to investigate the prevalence of peers’, parents’, and celebrities’ negative online behavior directed at celebrities and how often adolescents are exposed to this behavior.…”
Section: Discussionsupporting
confidence: 92%
“…This peer influence can be due to the changing socialization roles in adolescence, in which parents lose their exemplary function and the presence of peers in each other’s lives increases substantially (Furman & Collins, 2008). Various studies that compared the impact of parents and peers on adolescents’ behavioral intentions showed that adolescents attach more importance to the opinions and reactions of their friends and peers than to those of their parents and teachers (Heirman & Walrave, 2012; Mitchell, Petrovici, Schlegelmilch, & Szőcs, 2015; Pabian & Vandebosch, 2014).…”
Section: Peers’ Parents’ and Celebrities’ Norms Predict Online Aggrmentioning
confidence: 99%
“…Parental socialization is founded on the social learning theory. Socialization is defined as 'the process by which young people acquire skills, knowledge, and attitudes relevant to their functioning as consumers in the marketplace' (Mitchell et al, 2015). Social learning theory explains consumer socialization by focusing on environmental influences impinning on the individual.…”
Section: 2parenting Stylementioning
confidence: 99%
“…Moreover, they look for opportunities for skill development. Flexibility, sociability and familiarity with everything new are positive features of Generation Y and on the other hand, egocentrism, hedonism, self-confidence, irresponsibility and social networking "addiction" are considered negative ones (Wong et al, 2017;Gupta et al, 2016;Mitchell et al, 2015;Munir et al, 2015). People born between the years 1995 -2020 are known as Generation Z.…”
Section: Theoretical Frameworkmentioning
confidence: 99%